Policy research and the policy process: do the twain ever meet? - Garrett, James L.; Islam, Yassir (International Institute for Environment and Development, 1998)
In sum, the paper recommends a mixed-method approach to evaluation that looks at output, processes, and potential outcomes, rather than focusing on actual policy outcomes. This would better reflect how researchers produce their findings and policymakers actually use research and would help to identify how the organisation could improve its effectiveness